2018
DOI: 10.1037/rep0000210
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitants’ conscientiousness as a moderator of the intention–planning-behavior chain.

Abstract: Self-regulatory mechanisms such as action-facilitating planning strategies may be more efficient in conscientious rehabilitants. Conscientiousness reflects dispositional self-regulation and can be supportive when it comes to maintain difficult behaviors. Lack of Conscientiousness needs to be compensated by more intense support of rehabilitation patients, in order to plan appropriately and to act upon these plans in the face of barriers. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…While few studies have examined the role of personality in weight management for type 2 diabetes, there is more extensive evidence for the role of self-efficacy and diabetes distress ( 10 , 58 ). Two studies included in this review demonstrated the conceptual similarities, and interaction between, self-efficacy and conscientiousness ( 39 ), as well as diabetes distress and neuroticism ( 37 ), and their respective optimal and sub-optimal relationships with weight management.…”
Section: Discussionmentioning
confidence: 99%
“…While few studies have examined the role of personality in weight management for type 2 diabetes, there is more extensive evidence for the role of self-efficacy and diabetes distress ( 10 , 58 ). Two studies included in this review demonstrated the conceptual similarities, and interaction between, self-efficacy and conscientiousness ( 39 ), as well as diabetes distress and neuroticism ( 37 ), and their respective optimal and sub-optimal relationships with weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Medical rehabilitation and occupational health promotion should be tailored more strongly to the prevention of DP and to the special characteristics of the individuals in TDP [11,16]. Analyses of the importance of duration in TDP show that measures should be taken as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness was evaluated with the Big Five Inventory (John, Donahue, & Kentie, 1991), designed to measure the Big Five personality traits. In this study, we followed the same procedure of other recent studies (e.g., Lippke, Pomp, & Fleig, 2018) and included only the items related with the conscientiousness trait of the Big Five Inventory.…”
Section: Methodsmentioning
confidence: 99%